2004
DOI: 10.1097/01.md.0000119465.24818.98
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Vasculitis in Primary Sjögren Syndrome

Abstract: To analyze the different clinical and histologic types of cutaneous vasculitis in patients with primary Sjögren syndrome (SS), we investigated the clinical and immunologic characteristics of 558 consecutive patients with primary SS from our units and selected those with clinical evidence of cutaneous lesions, excluding drug reactions and xeroderma. All patients fulfilled 4 or more of the diagnostic criteria for SS proposed by the European Community Study Group in 1993. A total of 89 (16%) patients presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(58 citation statements)
references
References 69 publications
2
51
0
Order By: Relevance
“…18 Cryoglobulinemia can also be associated with an increased risk of lifethreatening multisystem vasculitis involving the central nervous system, kidneys, lungs, mesentery, and pancreas and severe cutaneous lesions, including ulcers and digital ischemia. 16 In summary, these findings underscore the importance of identifying palpable purpura and cryoglobulinemia in primary SS as an indicator of severe disease and poor prognosis.…”
Section: Cutaneous Vasculitismentioning
confidence: 93%
See 3 more Smart Citations
“…18 Cryoglobulinemia can also be associated with an increased risk of lifethreatening multisystem vasculitis involving the central nervous system, kidneys, lungs, mesentery, and pancreas and severe cutaneous lesions, including ulcers and digital ischemia. 16 In summary, these findings underscore the importance of identifying palpable purpura and cryoglobulinemia in primary SS as an indicator of severe disease and poor prognosis.…”
Section: Cutaneous Vasculitismentioning
confidence: 93%
“…16,17 In this condition, urticarial lesions appear as erythematous urticariform macules and are commonly seen on the upper extremities, face, and trunk. 16 Unlike common urticaria, the lesions of urticarial vasculitis in SS often persist for days, demonstrate petechiae, are painful to the touch instead of pruritic, and may heal with hyperpigmentation. 9,11 In a study of 52 patients with SS, 94% of those patients with histologically confirmed cutaneous vasculitis had leukocytoclastic vasculitis and 73% of these patients presented with palpable purpura.…”
Section: Cutaneous Vasculitismentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is related to the presence of cryoglobulinemia and high titers of rheumatoid factor and clinically manifests as ulcerative skin lesions, digital gangrene, mononeuritis multiplex, mesenteric arteritis, myositis, and glomerulonephritis [56]. Prednisone (1 mg kg −1 day −1 ), cyclophosphamide (0.5-1 g/m 2 monthly), and plasmapheresis are the mainstay of treatment [29].…”
Section: Vasculitismentioning
confidence: 99%